2018
DOI: 10.3168/jds.2018-14383
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing methods and protein content of the concentrate on the properties of milk protein concentrate with 80% protein

Abstract: In recent years, a large increase in the production of milk protein concentrates (MPC) has occurred. However, compared with other types of milk powders, few studies exist on the effect of key processing parameters on powder properties. In particular, it is important to understand if key processing parameters contribute to the poor solubility observed during storage of high-protein MPC powders. Ultrafiltration (UF) and diafiltration (DF) are processing steps needed to reduce the lactose content of concentrates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 36 publications
3
7
0
Order By: Relevance
“…This phenomenon results in a high viscosity at high protein content and hence would explain the high apparent viscosity values observed at higher TS content of MPC85 (18% protein at 21% TS) in this study. A similar increase in viscosity of reconstituted MPC80 (19%, 21% and 23% TS) was observed by Rupp, i.e., Reference [28] and by O'Donnell and Butler [29] for MPC (20-26% TS) samples. Bista et al [17] observed an exponential increase in viscosity as a function of TS content of reconstituted SMC (10-40% TS).…”
Section: Effect Of Total Solids Content On Apparent Viscosity Of Mpc85supporting
confidence: 81%
“…This phenomenon results in a high viscosity at high protein content and hence would explain the high apparent viscosity values observed at higher TS content of MPC85 (18% protein at 21% TS) in this study. A similar increase in viscosity of reconstituted MPC80 (19%, 21% and 23% TS) was observed by Rupp, i.e., Reference [28] and by O'Donnell and Butler [29] for MPC (20-26% TS) samples. Bista et al [17] observed an exponential increase in viscosity as a function of TS content of reconstituted SMC (10-40% TS).…”
Section: Effect Of Total Solids Content On Apparent Viscosity Of Mpc85supporting
confidence: 81%
“…Baldasso, Barros, and Tessaro (2011) used the DF mode to reduce the lactose content and to purify the protein content of the concentrate fraction, after obtaining a whey concentrated by UF. The purification of protein concentrated by UF from milk or whey by using DF mode was also reported by other authors (Cuartas-Uribe et al, 2009; Pan, Song, Wang, & Cao, 2011;Román et al, 2009;Rupp, Molitor, & Lucey, 2018).…”
Section: Introductionsupporting
confidence: 75%
“…This is most likely caused by differences in the protein content of the concentrates prior to spray drying (as mentioned in Section 3.1), with high protein concentrates possessing a higher viscosity, thereby generating larger droplets during the atomisation step of spray drying [36]. Rupp [37] reported that the D [4,3] of the MPC powder increased significantly from 31 to 50 μm with an increase in the protein content of the concentrate from 19 to 23% (w/w). Crowley [34] reported D90 values of 64.6 μm for MPC35 and 51.9 μm for MPC80 spray dried under similar conditions to the Powder particle size distribution analysis displayed a significant decrease in particle size with decreasing protein content ( Figure 2); MPC85 had a D [4,3] of 57.3 µm compared to 18.9 µm for MPC40 ( Table 2).…”
Section: Powder Particle Sizementioning
confidence: 99%